British Devolution and European Policy-Making - Bulmer, S. author. aut Link
XXV, 222 p.
Keywords: In 1999 the Blair government introduced British devolution as part of a major programme of constitutional reform. This development posed major questions concerning how relations with the European Union would be affected. Previously, policymaking in the UK had been centralized on Whitehall and Westminster. However, devolution to Scotland and Wales introduced new actors; the Scottish Executive and Parliament, and the National Assembly for Wales. This study explores the institutional changes designed to accommodate these devolved authorities, whilst maintaining a central role for the UK government.